Prevalence of chronic pain in low-income and middle-income countries: a systematic review and meta-analysis. (27th April 2015) - Jackson, Tracy; Thomas, Sarah; Stabile, Victoria; Han, Xue; Shotwell, Matthew; McQueen, Kelly
Abstract: Background: The global burden of chronic pain and disability could be related to unmet surgical needs. This systematic review and meta-analysis aims to characterise existing data regarding the prevalence and associations of chronic pain in low-income and middle-income countries; this is essential to allow better assessment of its relationship to pre-operative and post-operative pain as emergency and essential surgical services are expanded. Methods: According to PRISMA guidelines, we searched PubMed, PsycInfo, and Cochrane registries for articles published before Dec 31, 2013, using the search terms "pain AND (chronic OR persistent) AND (low income countries OR middle income countries OR LMIC OR Africa OR Asia OR Central America OR South America) AND (incidence OR prevalence)." We excluded paediatric populations (aged younger than 18 years) and those with acute pain or pain associated with known trauma, surgery, infection, or medical disorders. Findings: We identified 122 publications in 28 low-income and middle-income countries for systematic review; 79 surveys from general adult populations, elderly general populations, or workers. The prevalence of any type of chronic pain was 33% (95% CI 26–40) in the general adult population, 56% (36–75) in the general elderly population, and 35% (4–88) in workers; lower back pain was 18% (14–24), 31% (22–41), and 44% (33–55), respectively; headache 39% (27–53), 49% (37–60), and 52% (16–86), respectively; chronic daily headache 5% (3–7), not available, and 12% (8–19), respectively; musculoskeletal pain 26% (19–33), 39% (23–57), and 86% (56–93), respectively; joint pain 14% (11–18), 42% (26–60), and not available, respectively; and widespread pain 14% (9–22), 22% (9–46), and not available, respectively. Due to limited data, meta-analysis could only be done in single populations for some conditions. For general adult populations, chronic migraine was 10% (5–20); chronic tension-type headache was 4% (2–9); chronic pelvic pain or prostatitis was 11% (8–17); and fibromyalgia was 4% (3–7). In elderly general populations, prevalence of temporomandibular disorder was 7% (1–31) and abdominal pain was 6% (1–28). Heterogeneity in prevalence was largely secondary to variable definitions of pain chronicity. Associations were not readily amenable to meta-analysis; yet of the 122 publications, pain was described in association with disability in 50, female sex in 40, older age in 34, depression in 36, anxiety in 19, and multiple somatic complaints in 13. Interpretation: The prevalence of pain in low-income and middle-income countries is consistent with Global Burden of Disease data, with higher rates in the elderly general population and workers than in the general adult population. 28% of the global burden of disease that could be averted by surgery and safe anaesthesia might also be related to the chronic pain burden. Trauma, cancer, birth complications, congenital defects, and other surgical diseases potentially lead to chronic pain if not treated or if treated inadequately. This meta-analysis shows the range of chronic pain in low-income and middle-income countries, but has fallen short of revealing clear causes for the pain. The demonstration of the prevalence of chronic pain is essential as the era of global surgery begins, to allow benchmarking of this prevalence in the future as emergency and essential surgery services are expanded in low-income and middle-income countries. Funding: None.